Genetic dissection of leaf senescence in rice - Leng, Yujia; Ye, Guoyou; Zeng, Dali (MDPI, 2017)
Leaf senescence, the final stage of leaf development, is a complex and highly regulated process that involves a series of coordinated actions at the cellular, tissue, organ, and organism levels under the control of a highly regulated genetic program. In the last decade, the use of mutants with different levels of leaf senescence phenotypes has led to the cloning and functional characterizations of a few genes, which has greatly improved the understanding of genetic mechanisms underlying leaf senescence. In this review, we summarize the recent achievements in the genetic mechanisms in rice leaf senescence.